PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN LIMBAH PLASTIK DENGAN METODE ECOBRICK DI KELURAHAN BONEOGE KABUPATEN DONGGALA - Jufri, Muhammad; Moh. Zulfikri (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
Waste is a byproduct of human activity that is no longer needed, unwanted, or deemed disposable. Improper waste disposal behaviors can pollute the environment and diminish cleanliness. Ecobrick is a collaborative-based technology offering an innovative solution to reduce household plastic waste. In Boneoge Village, several environmental issues persist, including low public awareness and responsibility for maintaining cleanliness, lack of effective plastic waste management, and limited waste disposal facilities, resulting in waste accumulation and environmental pollution. To address these challenges, a community service team proposed training and mentoring programs for Boneoge residents to manage household plastic waste using the Ecobrick method. The long-term objective of this program is to foster community self-reliance in plastic waste management, creating opportunities for new businesses through marketable products. One proposed product is flower pots made from Ecobricks, which will be distributed to the community as examples and inspiration for developing other economically valuable items